Wide unroofed coronary sinus and cryptogenic stroke: a case report. Issue 6 (7th December 2020) - Babapoor-Farrokhran, Savalan; Kalla, Aditi; Bozorgnia, Behnam; Amanullah, Aman
Abstract: Background : Unroofed coronary sinus (UCS) is a rare congenital cardiac anomaly in which there is complete or partial absence of the roof of the coronary sinus (CS) resulting in a communication between the right and left atria. There are four types of UCS described in the literature. While usually asymptomatic and discovered incidentally on imaging, UCS can be the source of a brain abscess or paradoxical embolism. Case summary : A 62-year-old gentleman presented to the emergency department with sudden onset of right-sided weakness and subsequent unresponsiveness. His brain computed tomography (CT) was consistent with left-sided stroke. Transthoracic echocardiography was remarkable for a dilated CS and an agitated saline study was suggestive of an UCS. A gated cardiac CT with coronary angiography confirmed a wide communication between the CS and left atrium. Right heart catheterization did not show evidence of left to right shunt. He had no abnormal rhythm on telemetry monitoring throughout his hospital stay. Discussion : Unroofed coronary sinus is the least prevalent form of an atrial septal defect. Unroofed coronary sinus is usually asymptomatic and is diagnosed incidentally in imaging studies, however, it should be suspected in patients with cerebral emboli or evidence of left to right shunt with unexplained arterial desaturation. Transthoracic echocardiography is the most widely used imaging modality for the diagnosis of UCS but is limited in its ability to visualize the posterior cardiac structures such as the CS and pulmonary veins. Gated cardiac CT is a great diagnostic tool for UCS.